2020
DOI: 10.1016/j.mbs.2020.108436
|View full text |Cite
|
Sign up to set email alerts
|

Simulating COVID-19 in a university environment

Abstract: Residential colleges and universities face unique challenges in providing in-person instruction during the COVID-19 pandemic. Administrators are currently faced with decisions about whether to open during the pandemic and what modifications of their normal operations might be necessary to protect students, faculty and staff. There is little information, however, on what measures are likely to be most effective and whether existing interventions could contain the spread of an outbreak on campus. We develop a fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
133
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(140 citation statements)
references
References 22 publications
3
133
0
1
Order By: Relevance
“…In this simulation we have not included testing accuracy issues that are also very important [ 10 ]. Rapid tests that expedite the testing process, if used, may have larger accuracy issues that need to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this simulation we have not included testing accuracy issues that are also very important [ 10 ]. Rapid tests that expedite the testing process, if used, may have larger accuracy issues that need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…To test students and staff in elementary and secondary schools, some challenges and issues should be addressed: 1) the need for conducting significant number of tests for finding a small number of infected positive cases; 2) testing, especially frequent swab testing, may cause some pain or discomfort for children-although progress has been made towards less painful tests, such tests are not widely available; 3) almost all currently available tests have significant number of false-negative and falsepositive rates [9,10] that can cause confusion and stress; 4) tests may create a false sense of security among those tested; 5) conducting regular testing in schools is logistically challenging and requires additional resources, planning and operational burdens; 6) large scale testing of students may add more pressures to local public health testing capacities, and in particular, adding school testing may create more issues and increase waiting time for tests and test results; 7) tests are costly and the current PCR tests require specialized machinery and supplymore tests translates into more costs that need to be justified against the benefits that they generate; 8) the time between collecting a sample and receiving the test results is often too long-currently the test results are available after 1 to 6 days depending on the type of test and how many tests are being conducted [9], because the main goal of testing is to identify potential carriers and isolate them and those in close contact with them. As the time between sample collection and test results increases, the effectiveness of tests diminishes (For example, in the Province of Ontario, Canada, test results are returned between 1 to 3 days under normal conditions but this interval can increase to up to a week or even more under busy conditions); 9) public acceptance of mass testing particularly for younger kids in schools is low which may create push back; for example, a study conducted by Statistics Canada found that only 4 in 10 people support mandatory random COVID-19 testing and older adults are more supportive of this idea compared to younger people [11]; 10) privacy issues may arise in school testing-although the tests results can be kept private, subsequent follow up actions such as the temporary exemption from school, may disclose the identity of infected students.…”
Section: School Testing Challengesmentioning
confidence: 99%
“… 12 The potential for COVID-19 transmission in universities is significant, particularly shortly after the beginning of term when students return to campus. 4 , 5 Models demonstrate that universal testing may have a significant impact on control of the virus, depending on the ability of the setting to implement other control methods. 13 There is, however, no published study assessing the feasibility or acceptability of a universal programme for COVID-19 testing on a university campus.…”
Section: Discussionmentioning
confidence: 99%
“…3 It remains unclear how an outbreak might evolve on a university campus, but modelling studies suggest that students are highly interconnected, indicating significant potential for infectious disease transmission. 4 , 5 Colleges in the UK and USA have already reported outbreaks among the student population, necessitating closure in some cases. 6 The UK government is exploring community-wide testing for asymptomatic COVID-19 infection as a potential health protection tool, to enable outbreaks to be identified and controlled early.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also been devoted to the timing and heterogeneity of non-pharmaceutical interventions during the height of the pandemic [ 53 , 54 ]. Closely linked to this strand of work are epidemiological simulations for university campuses that inform university interventions, including contact tracing and quarantining [ 55 , 56 ]. Interventions are supported by communication efforts and recent research has focused on communication strategies [ 20 , 45 , 51 , 57 – 60 ], particularly on the use of social media and its positive effects on student satisfaction with university responses to the crisis [ 20 , 45 ].…”
Section: Introductionmentioning
confidence: 99%